On an estimate for the rearrangement of a function from the Muckenhoupt class $A_1$ - Leonchik, E. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain an exact estimate for a nonincreasing uniform rearrangement of a function of two variables from the Muckenhoupt class $A_1$.